Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I picked up Spivak's Calculus (3rd Edition) today and it seemed like a good idea to go through the section Basic Properties of Numbers. In this chapter, Spivak proves that

$$a \cdot 0 = 0$$

The proof looks simple:

$$a \cdot 0 + a \centerdot 0 = a \centerdot (0+0) = a \centerdot 0$$

My question is just as simple: How do I get from $a \centerdot 0 = 0$ to $a \centerdot 0 + a \centerdot 0 = a \centerdot (0+0)$?

share|improve this question
2  
I think you asked your question backwards. Spivak's proof involves two equalities. The first follows by the property $a b + a c = a(b+c)$. The second follows since by definition of $0$, $0+x = x$. –  Sam Lisi Mar 6 '12 at 16:30
    
You're both right. I'm a proof noob. :) Cheers! –  jamesbrewr Mar 6 '12 at 16:42
2  
He does not go from $a\cdot0=0$ to $a\cdot0+a\cdot0=a\cdot(0+0)$. That's backwards. He goes from $a\cdot0+a\cdot0=a\cdot(0+0)$ to something else, and from that something else eventually to $a\cdot0=0$. You don't go from what you're trying to prove to what you already know. You go in the other direction. –  Michael Hardy Mar 6 '12 at 16:53
add comment

5 Answers

up vote 11 down vote accepted

I am reading pp 7 of Spivak's Calculus (3rd Edition) right now.

What he's trying to do is to prove: $$ a\cdot 0 = 0$$ using $$ a\cdot(b+c) = a\cdot b + a\cdot c \tag{P9}$$ Let $b,c = 0$. We have: $$ a\cdot 0 = a\cdot (0+0) = a\cdot 0 + a\cdot 0. $$ By adding $(-a\cdot 0)$ to both sides of $ a\cdot 0 = a\cdot 0 + a\cdot 0 $ we get $$ a\cdot 0 + (-a\cdot 0) = a\cdot 0 + a\cdot 0 + (-a\cdot 0) $$ i.e. $$ 0 = a\cdot 0.$$

share|improve this answer
    
Since I'm new to these parts I can't vote yet, but I'll accept your answer. Thanks! –  jamesbrewr Mar 6 '12 at 16:43
add comment

$$a \centerdot 0 + a \centerdot 0 = a \centerdot (0+0) = a \centerdot 0$$ by distributivity.

Then we have that $$2(a\cdot 0) = a\cdot 0$$ which implies that $$a\cdot 0 =0$$

share|improve this answer
add comment

Since $0=0+0$, then $a\cdot 0 = a\cdot (0+0)$.

Since $\cdot$ distributes over $+$, whenever we have $x\cdot (b+c)$, this is equal to $x\cdot b + x\cdot c$. Applying this to $a\cdot(0+0)$, we get $a\cdot (0+0) = a\cdot 0 + a\cdot 0$.

So: $$\begin{align*} a\cdot 0 + 0 &=a\cdot 0 &\text{(because }x+0=x\text{ for all }x\text{)}\\ &= a\cdot (0+0) &\text{(because }0=0+0\text{)}\\ &= a\cdot 0 + a\cdot 0 &\text{(because }\cdot\text{ distributes over }+\text{)} \end{align*}$$ So we have $a\cdot 0 + 0 = a\cdot 0 + a\cdot 0$. Cancelling one $a\cdot 0$ (or adding $-(a\cdot 0)$ to both sides) we conclude that $0=a\cdot 0$.

share|improve this answer
    
So, essentially, what Spivak is doing is starting from an expression whose value is 0 (the expression $a \cdot 0 + a \cdot 0$) and proving that it's equal to $a \cdot 0$? –  jamesbrewr Mar 6 '12 at 16:38
    
@James Brewer: Spivak is starting from an expression which happens to evaluate to $0$, and proving that it does. I would have preferred if he had written the calculation in this order: $a\cdot 0=a\cdot(0+0)=a\cdot 0+a\cdot 0$ and therefore $\dots$. –  André Nicolas Mar 6 '12 at 16:46
    
@James: Spivak is starting from an expression, $a\cdot 0 + a\cdot 0$, which he doesn't know yet evaluates to $0$ (he hasn't proven that $a\cdot 0$ is $0$ yet), and proving that it is equal to $a\cdot 0$. From this, he concludes that $a\cdot 0$ is $0$; and from that you can conclude that $a\cdot 0+a\cdot 0$ evaluates to $0$. But we don't know that $a\cdot 0+ a\cdot 0$ evauates to $0$ until we prove that $a\cdot 0$ does. –  Arturo Magidin Mar 6 '12 at 16:48
    
The room just started to spin .. I think what I missed was that this proof is based off of a property previously listed in the text. See @J.D.'s (accepted) answer. –  jamesbrewr Mar 6 '12 at 16:50
add comment

That $a\cdot 0 + a\cdot 0 = a\cdot (0+0)$ is just using the distributive law. (From here you get $a\cdot (0+0) = a\cdot 0$ and then you just subtract $a\cdot 0$ on both sides.

share|improve this answer
add comment

You don't. He's not assuming $a \cdot 0 = 0$. He's proving that. So, you don't get from that to $a \cdot 0 + a \cdot 0 = a \cdot (0 + 0)$. How you do get that last statement is the distributive property. He then uses the property that 0 plus anything is that anything. In particular, $0 + 0 = 0$. Once you have that, we have $a \cdot 0 + a \cdot 0 = a \cdot 0$. Now, we use the fact that every number has an additive inverse, so we can add that to both sides, which is the same as subtracting $a \cdot 0$ from both sides. This leaves us with $a \cdot 0 = 0$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.